2017
DOI: 10.1111/1747-0080.12384
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative nutritional management of bariatric patients in Australia: The current practice of dietitians

Abstract: Reported preoperative screening practices were not consistent with the recommendations from the literature and current American guidelines. Further investigation into the difference in the nutritional management strategies and work environments is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
(101 reference statements)
0
10
0
Order By: Relevance
“…Preoperative dietary regimes greatly differ per country. [15][16][17] This study identified that particularly in the Netherlands, an LED was the most commonly prescribed diet while for example, Australia seemed to prefer VLEDs. 17 Both diets have shown to be effective in reducing liver volume 5,7 ; however, an LED might be advantageous as it avoids unnecessary energy restriction and may improve dietary compliance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Preoperative dietary regimes greatly differ per country. [15][16][17] This study identified that particularly in the Netherlands, an LED was the most commonly prescribed diet while for example, Australia seemed to prefer VLEDs. 17 Both diets have shown to be effective in reducing liver volume 5,7 ; however, an LED might be advantageous as it avoids unnecessary energy restriction and may improve dietary compliance.…”
Section: Discussionmentioning
confidence: 96%
“…13 According to the American Society for Metabolic and Bariatric Surgery (ASMBS) in 2016, there is no level A evidence about the most optimal type of preoperative weight loss program (ie, dietary or exercise strategies) and neither about the content and duration of this program. 14 A high variability in preoperative work up has since then been described in multiple countries, [15][16][17] yet it is unknown if and how this applies in the Dutch bariatric centers. The primary aim of this study was to identify variations in current weight loss goals prior to bariatric surgery.…”
mentioning
confidence: 99%
“…The impact of and adherence to clinical practice guidelines in dietetic practice was also investigated in this issue by Bourne et al Australian dietitians working with bariatric patients were surveyed for their adherence to the clinical practice guidelines for the nutritional, metabolic and nonsurgical management of bariatric surgery patients in the pre-operative stage. 5 This research employed a descriptive cross-sectional online survey to assess adherence to clinical practice guidelines. 13 The proportion of dietitians reporting routine screening of at-risk micronutrients varied between 32 and 45% in the regional and remote areas, whilst in the metropolitan areas there was a higher proportion of screening with reports between 55 and 65%.…”
Section: Editorialmentioning
confidence: 99%
“…Papers themed in this issue of Nutrition & Dietetics reflect the diversity of the different methodologies used to test their hypotheses within nutrition research, without the requirement for time intensive and costly traditional intervention studies such as randomised controlled trials (RCTs). These include systematic reviews, and qualitative methodologies such as online surveys and focus groups to monitor and assess efficacy. Also in this issue researchers have utilised existing RCTs to analyse secondary data, and report longitudinal observational studies to address existing gaps in the knowledge base in clinical dietetics.…”
mentioning
confidence: 99%
See 1 more Smart Citation